Semantic Group "Elements of Nature" In English and Uzbek Linguocultures (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study investigates the semantic group "Elements of Nature" in English and Uzbek linguocultures, focusing on how concepts related to nature are represented and interpreted in the two languages. Through a comparative analysis of linguistic structures, metaphors, and cultural references used to describe elements of nature, the research explores the similarities and differences in the conceptualization of natural phenomena in English and Uzbek.